Improving Learning Outcomes In The Subject Of Society In Economic Business Materials Through Cooperative Learning Methods In Students Class VC MI Sananul Ula Daraman Piyungan Bantul - Astuti, Budi (Journal of Social Science and Economics, 2023)
The quality of social studies learning in the classroom is less than optimal due to learning activities that are still teacher-centred. In delivering social studies lessons, teachers only refer to textbooks available at school, without any innovation, either in subject matter or learning methods. Teachers in teaching social studies as they are still use the lecture method, so social studies learning tends to be boring, unpleasant and less interesting for students. This classroom action research involved 26 students in the VC MI Sananul Ula Daraman class, with details of 16 male students and 10 female students. This classroom action research was carried out. Based on the results of the research and discussion, it can be concluded that the use of cooperative methods in learning activities can improve social studies learning outcomes.